Antidepressant Effect Of Andrographis Paniculata (Burm.F.) Wall. Ex Nees Methanolic Extract And Andrographolide On Chronic Unpredictable Stress (Cus) Zebrafish Model Via Metabolomics Approach - Aldurrah, Zenab (2023)
Depression affected at least 322 million people worldwide. Treatment for depression has been studied for a long time. However, the current antidepressants have many associated problems, such as delays in symptom resolution and relapse. Plants have been used as the main source of leads in drug discovery for decades. Andrographis paniculata (A. paniculata) is a widely used plant in Asian traditional medicine. This research investigates the effect of A. paniculata extract and its major compound, andrographolide on the chronic unpredictable stress (CUS) zebrafish model. A. paniculata methanol extract’s constituents was profiled using HPLC-ESI-MS/MS, and acute toxicity tests were analyzed before antidepressive evaluation. The behavioural study, i.e. open field test (OFT), social interaction test (SIT), and light dark test (LDT), were conducted to evaluate behavioural changes in the CUS group compared to the controls, A. paniculata (100 mg/L, immersion)-treated and fluoxetine (0.01 mg/L, immersion)-treated zebrafish. After the extract screening, the experiment was preceded by evaluating the antidepressive potential of andrographolide. Behavioural, cortisol and NMR-based metabolomics studies were evaluated in all groups. The behavioural study revealed a significant improvement in zebrafish locomotion after A. paniculata and andrographolide treatments. A significant reduction in cortisol levels (t-test, p=0.0003) were observed after andrographolide (25 and 50 mg/kg, i.p.) acute treatment.